2011
DOI: 10.3390/v3081485
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of RNAse T2 Expression by the HTLV-1 Viral Protein Tax

Abstract: Adult T-cell leukemia (ATL) is one of the primary diseases caused by Human T-cell Leukemia Virus type 1 (HTLV-1) infection. The virally-encoded Tax protein is believed to initiate early events in the development of this disease, as it is able to promote immortalization of T-cells and transformation of other cell types. These processes may be aided by the ability of the viral protein to directly deregulate expression of specific cellular genes through interactions with numerous transcriptional regulators. To id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Worth mentioning are some cytoskeletal and cytoskeleton-associated genes that were also disclosed by GO analysis under the term "development" and whose expression turned out to be affected in RNASET2-silenced cells, suggesting that they could possibly impact the in vivo cell differentiation pattern of the tumor cells, as disclosed in our xenograft model. Thus, the gene expression profiles we have documented in vivo in our ovarian model system are basically in agreement with the apparent functional behavior endorsed by RNASET2 that has been proposed before now (16,(21)(22)(23). We emphasize its role in creating an environmental milieu that is basically tumor suppressive.…”
Section: Ptx + Rnaset2supporting
confidence: 90%
See 1 more Smart Citation
“…Worth mentioning are some cytoskeletal and cytoskeleton-associated genes that were also disclosed by GO analysis under the term "development" and whose expression turned out to be affected in RNASET2-silenced cells, suggesting that they could possibly impact the in vivo cell differentiation pattern of the tumor cells, as disclosed in our xenograft model. Thus, the gene expression profiles we have documented in vivo in our ovarian model system are basically in agreement with the apparent functional behavior endorsed by RNASET2 that has been proposed before now (16,(21)(22)(23). We emphasize its role in creating an environmental milieu that is basically tumor suppressive.…”
Section: Ptx + Rnaset2supporting
confidence: 90%
“…Furthermore, a recent work from our group reported that the tumor suppressive role carried out by the RNASET2 gene in the Hey3Met2 ovarian cancer cell line model depends on the in vivo recruitment of cells from the macrophage lineage (15). Finally, a potential link between T2 ribonuclease-mediated modulation of the immune system and tumor suppression was recently established by a report showing that the Human T-lymphotropic virus 1 (HTLV-1) tax gene drives a strong down-regulation of the human RNASET2 gene (23). These experimental evidences, which collectively point to a role for RNASET2 in host immune response, are quite well recapitulated in the experimental data presented here.…”
Section: Ptx + Rnaset2mentioning
confidence: 98%
“…Furthermore, we observed that TNF-RII expression at the protein level had a different pattern than the expression at the mRNA level, which was particularly clear in BLV+PL animals. Such enigmatic inconsistencies between the amount and the pattern of changes at the transcript and protein levels have already been reported (Tian et al 2004, Stark et al 2006, Sarro et al 2010 and it is also known that viruses can influence the amount of mRNA and protein in host cells and modify the synthesis and metabolism of these molecules or influence their stability (Bolinger et al 2010, Polakowski et al 2011, Liu et al 2012. Mechanisms used by BLV interfering with a multistage process of host gene expression are still poorly investigated and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro DNA-binding assays have been extensively used to characterize interactions between NHEJ core machinery and DNA termini (88)(89)(90)(91)(92)(93). We previously used immobilized-DNA-binding assays to assess protein-DNA interactions (94). We tested whether HBZ influences the recruitment of Ku70 or Ku80 to DSBs using immobilized-DNA-binding assays in which a biotinylated double-stranded, blunt-end DNA fragment (35 bp) was immobilized on streptavidin-coupled beads and incubated with nuclear extracts from HEK 293T cells transiently overexpressing HBZ-WT, HBZ-ΔAD, or HBZ-ΔbZIP.…”
Section: Resultsmentioning
confidence: 99%